1955
DOI: 10.1136/adc.30.153.460
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Thyrotoxicosis, Hepatosplenomegaly and Jaundice in Two Infants of Exophthalmic Mothers

Abstract: This paper describes two infants with congenital enlargement of the thyroid and hepatosplenomegaly. One infant died at birth from obstetrical causes, the other lived for 33 days, during which time he was thyrotoxic and jaundiced. Though the first infant was not jaundiced, and, naturally, showed no signs of thyrotoxicosis, we consider that he showed all the other features of the syndrome. Maternal History Both infants were the offspring of mothers who had undergone thyroidectomy for Graves's disease, two years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1960
1960
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Hepatic manifestations of neonatal hyperthyroidism were reported as early as 1955 and are recognized, though less common, manifestations of neonatal Graves' disease [14]. Literature review identified 11 case reports discussing the hepatic manifestations of neonatal Graves' disease [14]- [24].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic manifestations of neonatal hyperthyroidism were reported as early as 1955 and are recognized, though less common, manifestations of neonatal Graves' disease [14]. Literature review identified 11 case reports discussing the hepatic manifestations of neonatal Graves' disease [14]- [24].…”
Section: Discussionmentioning
confidence: 99%
“…Such a d isp arity could well occur b y chance, b u t it is o f in te re st t h a t in tw o fam ilies described b y D avies (1943), congenital goitre (w ith o u t h y p e rth y ro i dism ) affected m ales only. Skelton and Gans (1955) suggested th a t the fem ale foetus m ig h t be b e tte r e q u ip p ed to n eu tralise in som e w ay its m o th e r's excess th y ro id -stim u la tin g horm one.…”
Section: The In Fa N Ts' ' Historiesmentioning
confidence: 99%